2015
DOI: 10.1083/jcb.201411008
|View full text |Cite
|
Sign up to set email alerts
|

KCC2 regulates actin dynamics in dendritic spines via interaction with β-PIX

Abstract: In neurons, KCC2 controls glutamatergic synaptogenesis and regulates actin polymerization in dendritic spines by binding β-PIXb and attenuating its GEF activity toward small GTPase Rac1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 62 publications
5
51
0
Order By: Relevance
“…This effect was proposed to be mediated by KCC2’s ability to reduce membrane potential upon activation of GABA A receptors, thereby decreasing the activity of voltage sensitive calcium channels (VSCCs) and overall Ca 2+ dynamics in the cell (Bortone and Polleux, 2009). KCC2 has also been shown to interact with the actin cytoskeleton to regulate spine formation, an activity that appears to be independent from its chloride transport function (Li et al, 2007; Llano et al, 2015). Further work will be required to determine whether KCC2 regulates tangential to radial switch and laminar dispersion of cortical GABAergic interneurons through its effects on GABA signaling, the cytoskeleton or some other mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was proposed to be mediated by KCC2’s ability to reduce membrane potential upon activation of GABA A receptors, thereby decreasing the activity of voltage sensitive calcium channels (VSCCs) and overall Ca 2+ dynamics in the cell (Bortone and Polleux, 2009). KCC2 has also been shown to interact with the actin cytoskeleton to regulate spine formation, an activity that appears to be independent from its chloride transport function (Li et al, 2007; Llano et al, 2015). Further work will be required to determine whether KCC2 regulates tangential to radial switch and laminar dispersion of cortical GABAergic interneurons through its effects on GABA signaling, the cytoskeleton or some other mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…βPix-b has higher GEF activity than βPix-a In addition to the differences in spine localization between βPix-a and -b, their differential GEF activity for Rac1 may contribute to the distinct phenotypes of βPix-a and -b in spine formation. Llano et al (2015) showed that βPix-b-induced Rac1 activation is drastically inhibited in neurons expressing βPix-b construct devoid of DH domain (βPix-bDHm), indicating that the DH domain of βPix-b has GEF activity for Rac1. Here, we tested whether there is a difference in GEF activity between βPix-a and -b.…”
Section: βPix-b Enhances Spine Development and Synapse Formation Thromentioning
confidence: 99%
“…2007; Llano et al . 2015), and in mature excitatory synapses KCC2 restricts AMPAR (AMPA‐type glutamate receptor) lateral diffusion in dendritic spines (Gauvain et al . 2011).…”
Section: Gpcr Modulation: a Brief Overviewmentioning
confidence: 99%